The Influence Of Product Innovation And Perceived Quality On Purchase Decisions Of Somethinc Lip Glaze - Aulia Nur Pratiwi; Annisa Retno Utami (proceedings.icesy, 2026)
This study aims to analyze the influence of product innovation and perceived quality on consumer purchase decisions for Somethinc Forever Stay Comfort Lip Glaze. The research employed a quantitative associative approach using a survey method. Data were collected through structured questionnaires distributed to 96 respondents who had purchased and used the product. Data analysis was conducted using SPSS, including validity and reliability tests, multiple linear regression analysis, partial tests (t-test), simultaneous tests (F-test), and coefficient of determination (R²). The results indicate that product innovation and perceived quality have a positive and significant effect on purchase decisions, both partially and simultaneously. The coefficient of determination shows that 60% of purchase decision variation is explained by product innovation and perceived quality. These findings suggest that relevant product innovation and consistent perceived quality play a crucial role in strengthening consumer confidence and driving purchase decisions. Therefore, cosmetic companies should continuously integrate innovation and quality improvement strategies to remain competitive in the Indonesian cosmetic market.